Determinants for return to work among sickness certified patients in general practice - von Celsing Anna-Sophia; Svärdsudd Kurt; Eriksson Hans-G; Björkegren Karin; Eriksson Margaretha; Wallman Thorne (BMC, 2012)
Abstract Background Long-term sickness absence is one of the main risk factors for permanent exit out of the labour market. Early identification of the condition is essential to facilitate return to work. The aim of this study was to analyse possible determinants of return to work and their relative impact. Methods All 943 subjects aged 18 to 63 years, sickness certified at a Primary Health Care Centre in Sweden from 1 January until 31 August 2004, were followed up for three years. Baseline information on sex, age, sick leave diagnosis, employment status, extent of sick leave, and sickness absence during the year before baseline was obtained, as was information on all compensated days of sick leave, disability pension and death during follow-up. Results Slightly more than half the subjects were women, mean age was 39 years. Half of the study population returned to work within 14 days after baseline, and after three years only 15 subjects were still on sick leave. In multivariate proportional hazards regression analysis the extent of previous sick leave, age, being on part-time sick leave, and having a psychiatric, musculoskeletal, cardiovascular, nervous disease, digestive system, or injury or poisoning diagnosis decreased the return to work rate, while being employed increased it. Marital status, sex, being born in Sweden, citizenship, and annual salary had no influence. In logistic regression analyses across follow-up time these variables altogether explained 88-90% of return to work variation. Conclusions Return to work was positively or negatively associated by a number of variables easily accessible in the GP's office. Track record data in the form of previous sick leave was the most influential variable.